Malaysian learners' conceptions of their learning processes and their perceptions of their English as a second language (ESL) courses in a tertiary distance learning context - Thang, Siew Ming (2001)
There is an ever-increasing demand for higher education in Malaysia. In order to fulfil this demand, the government has introduced numerous measures to expand higher education opportunities. These plans have included the expansion and development of distance education. Prior to the mid-1992, only one public university, i.e., University Sains Malaysia, offered distance learning courses. Presently, six out of the eight public universities are participating in off-campus/distance education schemes. The distance learning courses offered by these universities can be divided into two categories: content courses and language courses. Research into the effectiveness of the distance learning content courses has been undertaken, but so far, no research has been carried out on the distance learning language courses. The purpose of this thesis is to investigate the effectiveness of the distance learning English Proficiency Programme of one of these universities, i.e., Universiti Kebangsaan Malaysia, in meeting the learning needs of the distance learners. This thesis undertakes three studies that investigate the distance learners' conception of their learning styles in learning English, their approaches to studying in general and their perceptions of their English Proficiency Courses. On-campus learners are included to enable a comparison to be made. The thesis adopts an integrated approach comprising both qualitative and quantitative methodologies. The instruments used are questionnaires and interviews. The questionnaires are adapted from those of Willing's (1988) and Entwistle and Ramsden's studies (1983). The semi- structured interviews are used to elicit information regarding distance learners' views of their English Proficiency Courses. The data are analysed statistically (with the used of SPSS 9.0) as well as qualitatively. The purpose of this research is to devise a strategy for developing a distance learning English as a Second Language programme suitable for university learners in Malaysia and, possibly, to provide insights which might be applicable to other similar contexts.